Microcontroller based Earthquake indicator and measurement system - Das, Siddharth; Chatterjee, Sumanta; Paul, Apurba (International Journal of Computer Sciences and Engineering, 2025)
“Prevention is better than cure”. This statement goes perfect with the events whose probability of occurrence is highly possible. Earthquake is one of such disaster that comes as an evil fate and sweeps away precious human lives and civilization, it is that unpredictable phenomenon whose occurrence cannot be avoided, but at least we can take measures to minimize the adverse effect of its consequences. The main objective of this research paper is to design a circuit which will acts as an earthquake indicator and prevents further damage. Arduino microcontroller and a highly-sensitive ADXL335 accelerometer are used to accomplish the circuit.